Long Service Ability In Badminton Games Of Grade V Students Of Mawas State Elementary School - Ridwan, Andi (Sains Global Institut, Indonesia, 2024)
This research is descriptive. This study aims to determine the level of long-service ability in badminton games of grade V students of Mawas Elementary School. The population is some grade V students. This sampling technique uses Purposive sampling with a sample size of 17 students. The data analysis technique used is quantitative descriptive analysis. The results of the study showed that the level of interest in Long Service Ability Analysis in Badminton Games of Grade V Students of Mawas Elementary School obtained a very high category of 3 students or 17.65%, a high category of 8 students or 47.06, and a low category of 6 students or 35.29%. Based on the level of interest in Long Service Ability Analysis in Badminton Games of Grade V Students of Mawas Elementary School, the highest frequency is in the high category